Estudio del crecimiento y la produccion en mandarinas (Citrus reticulata) - Torres, M.=700 1 Frometa M, E.
(Es, En)
Ilus., 6 ref.
Keywords: CITRUS RETICULATA; CRECIMIENTO; PRODUCCION; CUBA; MANDARINAS